RF System Design of Transceivers for Wireless Communications - Gu, Qizheng. (Springer US : Imprint: Springer, 2005)
RF System Design of Transceivers for Wireless Communications is for RF Engineers and, in particular, those engineers focusing mostly on RF systems and RFIC design. The author develops systematic methods for RF systems design, complete with a comprehensive set of design formulas. Its focus on mobile station transmitter and receiver system design also applies to transceiver design of other wireless systems such as WLAN. The book is filled with detailed wireless systems design information, and addresses specifications that are critical for the design process. Additional highlights include: * Fundamental information on communications, signal and system theories * Coverage of superheterodyne, direct-conversion, low-IF, and band-pass sampling radio architectures * Frequency planning, system link budgeting, and performance evaluation of transmitters and receivers * Nonlinearity effect analyses involving intermodulation, interferer blocking, spectrum regrowth and modulation * Approaches for specifying RF ASICs on which mobile systems are built * AGC systems, ADC dynamic range consideration and power management are addressed * In-depth treatment of both theoretical and practical aspects of mobile station RF system design This comprehensive reference work covers a wide range of topics from general principles of communication theory, as it applies to digital radio designs to specific examples on implementing multimode mobile systems. Wireless engineering professionals will definitely find this an invaluable reference book.